2010
DOI: 10.1007/s13197-010-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pure starter cultures on physico-chemical and sensory quality of dry fermented Chinese-style sausage

Abstract: Dry fermented Chinese-style sausages prepared in laboratory inoculating with Lactobacillus casei subsp.casei-1.001, Pediococcus pentosaceus-ATCC 33316, Staphylococcus xylosus-12 and without starter culture randomly sampled at 0, 3, 10, and 24 days of ripening were analyzed for physico-chemical and sensory qualities. A signifi cant (p<0.05) decrease in moisture content of sausage during ripening was observed, whereas other major chemical parameters remained unchanged. The microbial fermentation resulted in decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
(47 reference statements)
2
12
1
Order By: Relevance
“…Among these genera Lactobacillus is regarded as one of main bacteria that produce plenty of lactic acid and one of dominant LAB in vegetable fermentations (Xiong et al, 2013). Some researchers have demonstrated that Lactobacillus is contributed to the depletion of nitrite accumulated during fermentation in paocai (Yan et al, 2008;Rai et al, 2010). Then…”
Section: Resultsmentioning
confidence: 99%
“…Among these genera Lactobacillus is regarded as one of main bacteria that produce plenty of lactic acid and one of dominant LAB in vegetable fermentations (Xiong et al, 2013). Some researchers have demonstrated that Lactobacillus is contributed to the depletion of nitrite accumulated during fermentation in paocai (Yan et al, 2008;Rai et al, 2010). Then…”
Section: Resultsmentioning
confidence: 99%
“…The firmness of the pickled vegetable decreased quadratically with fermentation time, as indicated by the increasing depth the probe could penetrate the tissue, that is from 43.16 to 59.31 in fermentation was higher than those in the batch that was inoculated with mixed cultures (Fig 1 B). The high population of LAB at the initial stage of fermentation had an important role in inhibiting growth of contaminants even after fermentation had started (Hu et al 2007;Rai et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the faster the production of lactic acid, the faster the pH decreased (Tolonen et al 2002;Wiander and Ryhanen 2005), thus the faster the completion of In order to control the fermentation, LAB starter cultures have been used in the fermentations of sauerkraut, olives, cucumber, sausages, and other fermented products (Fleming et al 2001;Hu et al 2007;Rai et al 2006;Zdolec et al 2008). Volume 7, 2013 Microbiol Indones 5 were 3.2 and 3.3 (neither liked nor disliked).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Turkish Standard Institute states that quality ripened sausages should have pH values between 4.7 and 5.4 in Turkish Sucuk Standard and the pH values of all Sucuk samples were between in this range. The decline in the pH value during the first days of ripening (fermentation) is very important for the production of safe and high quality sausages due to the inhibition of undesired bacteria, conversion and stabilization of colour, and formation of desired flavour (Incze 1992;Rai et al 2010;Thomas et al 2010;Surehkumar et al 2010). The initial dry matter contents of control, 10%K, 20%K, 30%K, 40%K and 50%K products were 40.13, 39.36, 38,60, 37.84, 37.04 and 36.27 and the final dry matter contents were 65.80, 66.28, 64.80, 64.30, 63.77 and 63.28, respectively.…”
Section: Resultsmentioning
confidence: 99%